IMPLEMENTATION OF ACTIVE LEARNING STRATEGIES WITH A HUMANISTIC APPROACH IN ISLAMIC EDUCATION SUBJECTS AND THEIR EFFECT ON STUDENT MOTIVATION AND LEARNING OUTCOMES AT SMP NEGERI 4 PALEMBANG - Widyawati, Anggun; Amilda, Amilda; Fauzi, Muhammad; Adeoye, Moses Adeleke (Jurnal Asy-Syukriyyah, 2025)
This research investigates the implementation and effects of active learning strategies integrated with humanistic pedagogical approaches on student learning motivation and cognitive achievement in Islamic Religious Education (PAI) at SMP Negeri 4 Palembang.. Data collection instruments included a 25-item motivation questionnaire (Cronbach's α = 0.976) and an 18-item learning outcomes test (Cronbach's α = 0.737), both satisfying validity and reliability requirements. Independent samples t-tests revealed significant between-group differences in learning motivation (t = -8.295, p = 0.000, experimental M = 112.58 vs. control M = 95.91) and learning outcomes (t = -2.677, p = 0.009, experimental M = 89.03 vs. control M = 82.21). Multivariate Analysis of Variance (MANOVA) confirmed simultaneous significant effects on both dependent variables (Wilks' Lambda = 0.461, p = 0.000, Partial Eta² = 0.539), indicating large practical effect sizes. The findings substantiate that integration of active learning strategies with humanistic principles produces coherent, synergistic enhancements in both affective motivation and cognitive achievement dimensions. Results suggest that pedagogical approaches addressing simultaneous cognitive engagement and emotional support facilitate comprehensive student development aligned with Islamic education's holistic philosophical foundations emphasizing character formation alongside intellectual growth.